Pengaruh Penerapan E-Registration, E-Filing E-Billing Dan Preferensi Risiko Terhadap Kepatuhan Wajib Pajak Orang Pribadi Dengan Pemahanan Internet Sebagai Variabel Moderasi Di Kantor Pelayanan Pajak (KPP) Karanganyar - Tomy Hermansyah; Achyani, Fatchan (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to examine the influence of the implementation of e-registration, e-filing, e-billing systems, and risk preferences on individual taxpayer compliance at KPP Karanganyar, with internet literacy as a moderating variable. The method used is a quantitative approach with primary data collection techniques through questionnaires. The study population includes taxpayers registered at KPP Karanganyar, and the sample was selected using purposive sampling. The results of the study indicate that e-registration, e-billing, and risk preferences do not significantly affect taxpayer compliance. However, e-filing has been proven to improve taxpayer compliance. Additionally, internet literacy as a moderating variable does not strengthen the relationship between e-registration, e-filing, e-billing, or risk preferences and taxpayer compliance. This study contributes to the understanding of factors influencing taxpayer compliance and the role of internet literacy in electronic taxation systems.